Regulation of Tumor Initiation by the Mitochondrial Pyruvate Carrier - Bensard, Claire L.; Wisidagama, Dona R.; Olson, Kristofor A.; Berg, Jordan A.; Krah, Nathan M.; Schell, John C.; Nowinski, Sara M.; Fogarty, Sarah; Bott, Alex J.; Wei, Peng; Dove, Katja K.; Tanner, Jason M.; et al. (Cell metabolism, 2020)
Although metabolic adaptations have been demonstrated to be essential for tumor cell proliferation, the metabolic underpinnings of tumor initiation are poorly understood. We found that the earliest stages of colorectal cancer (CRC) initiation are marked by a glycolytic metabolic signature, including downregulation of the mitochondrial pyruvate carrier (MPC), which couples glycolysis and glucose oxidation through mitochondrial pyruvate import. Genetic studies in Drosophila suggest that this downregulation is required because hyperplasia caused by loss of the Apc or Notch tumor suppressors in intestinal stem cells can be completely blocked by MPC overexpression. Moreover, in two distinct CRC mouse models, loss of Mpc1 prior to a tumorigenic stimulus doubled the frequency of adenoma formation and produced higher grade tumors. MPC loss was associated with a glycolytic metabolic phenotype and increased expression of stem cell markers. These data suggest that changes in cellular pyruvate metabolism are necessary and sufficient to promote cancer initiation. [Display omitted] •Intestinal tumors exhibit low MPC expression•MPC inactivation is sufficient to promote intestinal tumor formation in mice and flies•MPC overexpression in the fly is sufficient to prevent oncogene-induced tumorigenesis•MPC expression correlates negatively with expression of Wnt/β-catenin target genes A hallmark of cancer is altered metabolism in tumor cells; however, it is unclear whether cancer initiation also requires metabolic changes. Bensard et al. demonstrate that constitutive enforcement of a glycolytic program through inactivation of the mitochondrial pyruvate carrier (MPC) is necessary and sufficient to drive intestinal tumor formation.